Synthesis and Dielectric Properties of Four-Layered Aurivillius SrBi4Ti4O15 Doped Nd3+ and Mn4+ - Sestry Misfadhila; Evi Adhelina; Yestria Rilda; Syukri Arief; Zulhadjri Zulhadjri (ALCHEMY Jurnal Penelitian Kimia, 2016)
Synthesis of four-layered Aurivillius compound doped with Nd3+ and Mn4+ cations, SrBi3.5Nd0.5Ti4-xMnxO15 (x = 0; 0.5; 1) was carried out using molten salt method with a mixture of Na2SO4/K2SO4 as a flux. The synthesized products were characterized using X-ray diffraction (XRD) and refined by Le Bail technique. The results of XRD analysis show that the four-layered Aurivillius compound formed, however there are additional peaks identified as perovskite and Bi7.68Ti0.32O12.16  phases for x = 0 and perovskite and Sr4Ti3O10phases for x = 0.5 and 1. The results of refinement show that four-layered Aurivillius phase formed has orthorhombic symmetry with A21am space group. Scanning Electron Microscopy (SEM) shows the plate like morphology that are characteristic of Aurivillius compound. Dielectric constant of the samples show increasing value as increasing of Mn4+ concentration.